The relationship between bar velocity and the strength moves down to the floor in the snatch for senior players - Jasim, Moaid (Journal of Physical Education, 2019)
The importance of the study deals with the exirt of the lationship between be velocity and weightlifter effort from leg muscle to the floor during perform snatch. The problem of the study in the failure of snatch and clean and jerk. Because they depend on the isolation of maximum strength training and speed. The goals of the research are: 1. To study the volume of strength moves to the floor, and bar velocity for the player when perform snatch. 2. To identify the relationships of strength velocity and time variables The researcher concluded: 1. The time was not convenience with the result strength during lift. 2. The training with high resistance and low velocity improve power for the Wright lifters